Distribusi dan Ketimpangan Pendapatan Petani di Desa Kuok Kecamatan Bangkinang Barat Kabupaten Kampar - Ahmad Rifafi (Jurnal Sagu, 2005)
Thestudy aimed to analyze the income distribution and inequality of farmer housthold in Kuok village,Kampar District The data used in the study were collected from survey in June to November 2004. The resultof study shows that agricultural income was dominated by income distribution of farmer household.Agricultural income has the highly positive correlation to increase the total income of farmer household.Income distribution of household was high inequality, shown by the gini coefficient of 0.437. According to thefactor inequality weights of resource incomes, agricultural income contributed the largest portion to the totalincome inequality of farmer household. Income from paddy and livestock increased the income inequality ofagricultural income, and income from rubber decreased the inequality of agricultural income. The salaryfrom government employment contributed the largest portion to non-agricultural income incqualitj, and self-employment .«ich as earnings from shop keeping, unskilled labor, private sector, and other activities decreasedthe non-agricultural income inequality.